2008
DOI: 10.21314/jop.2008.043
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and measuring multivariate operational risk with Lévy copulas

Abstract: Simultaneous modelling of operational risks occurring in different event type/business line cells poses a serious challenge for operational risk quantification. Here we invoke the new concept of Lévy copulas to model the dependence structure of operational loss events. We explain the consequences of this dependence concept for frequencies and severities of operational risk in detail. For important examples of the Lévy copula and heavy-tailed GPD tail severities we derive first order approximations for multivar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 9 publications
0
37
0
3
Order By: Relevance
“…The algorithm is a two-stage based on scenario aggregation algorithm. We compare its performance with approach based on the ParetoLévy copulas [3].…”
Section: Operational Risk Modeling Involves Various Problemsmentioning
confidence: 99%
See 1 more Smart Citation
“…The algorithm is a two-stage based on scenario aggregation algorithm. We compare its performance with approach based on the ParetoLévy copulas [3].…”
Section: Operational Risk Modeling Involves Various Problemsmentioning
confidence: 99%
“…They allow for description of more complex dependences between variables than the Pearson correlation and can be implemented in the Monte Carlo framework used in LDA [15]. Therefore copulas have been frequently used to model dependences in operational risk [3,5,16,17]. …”
Section: Copulas and Their Applicationmentioning
confidence: 99%
“…Copula models have been introduced to allow for modelling the dependence structure between ORCs. Böcker and Klüppelberg (2008) undertook the simultaneous modelling of operational risks occurring in different event type/business line cells. They found that this analysis posed serious challenges for operational risk quantification and they invoked Lévy copulas to model operational loss events dependence structures.…”
Section: Calculating Economic Capitalmentioning
confidence: 99%
“…Pueden existir varios tipos de dependencia en las celdas, y Böcker y Klüppelberg [32] realizan 1 Estos modelos son llamados así porque las colas de las distribuciones son muy pesadas y puede conllevar a estimación de cargos de capital absurdos mediante VaR. Bajo estos modelos, medidas como expected shortfall no tienen sentido.…”
Section: Cópula Como Método De Agregación De Riesgosunclassified
“…Para modelar dependencia entre frecuencia y severidad en las diferentes celdas, [32] usan la cópula Lévy. Para ello, asumen que el proceso de frecuencia sigue un proceso de Poisson homogéneo y todas las severidades son iid.…”
Section: Utilizan Datos De Un Banco (Del the 2004 Operational Risk Lounclassified